The 2008 Presidential Elections
XII, 259 p.
Keywords: The election of Barack Obama fundamentally changed America's relationship with the outside world. Written by a mix of scholars and practitioners, the chapters cover the entire electoral process and analyze what Obama's victory suggests about the development of America, socially, economically, and in its foreign relations.